Agglomeration, vertical specialization, and the strength of industrial linkages - Jan Kranich (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
This paper picks up the seminal model of Venables (1996) and provides a quantifying concept for the sectoral coherence in vertical-linkage models of the New Economic Geography. Based upon an alternative approach to solve the model and to determine critical trade cost values, this paper focuses on the interdependencies between agglomeration, specialization and the strength of vertical linkages. A central concern is the idea of an 'industrial base' which is attracting linked industries but is persistent to relocation. As a main finding, the intermediate cost share and substitution elasticity basically determine the strength of linkages. Thus, these parameters affect how strong the industrial base responds to changes in trade costs, relative wages and market size.
Keywords: F12; 330; New economic geography; vertical linkages